2015
DOI: 10.1523/jneurosci.4037-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Single-Unit Recordings in the Macaque Face Patch System Reveal Limitations of fMRI MVPA

Abstract: Multivariate pattern analysis (MVPA) of fMRI data has become an important technique for cognitive neuroscientists in recent years; however, the relationship between fMRI MVPA and the underlying neural population activity remains unexamined. Here, we performed MVPA of fMRI data and single-unit data in the same species, the macaque monkey. Facial recognition in the macaque is subserved by a well characterized system of cortical patches, which provided the test bed for our comparison. We showed that neural popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 33 publications
6
112
0
Order By: Relevance
“…Moreover, the view decoding made mirror-symmetric mistakes in AL and AM, just as we had found earlier in the units (Fig. 2F) (Dubois et al 2015). This suggests that cells tuned to the same view are spatially clustered in each face patch.…”
Section: Functional Architecturesupporting
confidence: 80%
“…Moreover, the view decoding made mirror-symmetric mistakes in AL and AM, just as we had found earlier in the units (Fig. 2F) (Dubois et al 2015). This suggests that cells tuned to the same view are spatially clustered in each face patch.…”
Section: Functional Architecturesupporting
confidence: 80%
“…In addition, recent work combining electrophysiology and fMRI in non-human primates has demonstrated that the sensitivity of MVPA is limited by the spatial characteristics of the neuronal representations that code for particular features, such that some kinds of neuronal patterns may be more difficult to decode using MVPA than others 33 . Finally, it is important to stress that, like standard neuroimaging approaches, MVPA and RSA approaches do not inform about causal mechanisms.…”
Section: Representational Analysesmentioning
confidence: 99%
“…Why the anterior temporal poles were not observed in our results, despite their likely involvement in multimodal/amodal representations of individuals 1 , remains unclear. This is unlikely due to signal-to-noise ratio differences in anterior compared to posterior temporal regions 22 as we found above-chance classification for other classification schemes in some quite anterior temporal lobe clusters (Fig. 2).…”
Section: Discussionmentioning
confidence: 69%
“…Importantly, the limitations of a single stimulus per identity per modality discussed above do not bear on the interpretation of the cross-modal results: the training and test sets of fMRI data were acquired not just on different stimuli from the same identities, as has been performed by other 'unimodal' studies [19][20][21][22]24,25 but on different stimuli in different sensory modalities -arguably a more complex generalization problem than that posed by different person-related stimuli in the same modality 26 . So the cross-classification observed here is a 'true' identity classification, as opposed to the stimulus classification of our within-modality results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation